Evaluation of direct esterification of fatty acid derivative of Kojic acid in co-solvent system: a statistical approach - Ahmad Norddin, Fatin Amirah; Syed Azhar, Sharifah Nurfadhlin Afifah; Ashari, Siti Efliza (Omics Publishing, 2017)
The present work deals with direct esterification method to synthesize Kojic acid using immobilized lipase as a biocatalyst in acetonitrile with the addition of dimethylsulfoxide (DMSO) as a solubilizing agent Co-solvent respectively. To increase the esterification yield of KMO, modifications of the process were evaluated, including the use of a cosolvent and the use of Novozyme 435 (Candida antarctica) as a catalyst. The KMO synthesis has been developed and optimized by using Response Surface Methodology (RSM) with Central Composite Rotatable Design (CCRD). The optimized condition of enzyme was 3.35 wt% and 1:3.64 molar ratio of kojic acid and oleic acid at 82.39°C for 255.24 min of reaction. With these condition, the maximum percentage yield was 42.73% with R2 value of 0.866914 and indicated that 86.69% of the variability in the response could be explained by the model. The model was significant and fitted well with the experimental data and the lack of fit was not significant. The efficacy for cosmetic application was successfully tested and showed as non-irritating with a Human Irritancy Equivalent score between 0.55-0.83 which safe to be applied in cosmetic ingredient.